Muscle Cell and Tissue - Current Status of Research Field 2018
DOI: 10.5772/intechopen.75201
|View full text |Cite
|
Sign up to set email alerts
|

Methods and Model Systems Used to Study Pregnant Human Uterine Smooth Muscle

Abstract: Successful pregnancy necessitates that the human uterus is maintained in a relaxed, quiescent state for the majority pregnancy, before ultimately transforming to a contractile phenotype capable of powerful, coordinated contractions to facilitate parturition. The exact mechanisms that regulate this transition are yet to be fully understood, and as such, we still do not understand the molecular mechanisms that trigger the onset of human labor. This is in large part due to the ethical considerations associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
(214 reference statements)
0
3
0
Order By: Relevance
“…Based on the in vitro inhibition of Ca 2+ -mobilization from the myometrial cells and in vitro uterine-selectivity compared to aortic VSMCs by mundulone and MA, we chose to examine their tocolytic ability and confirm uterine-selectivity at the tissue level. A well-established and widely utilized ex vivo isometric contractility assay was used to examine the effect of mundulone and MA on contractile activity of term pregnant mouse myometrial tissue [3,[33][34][35][36][37][38][39]. During our initial experiments, we observed the precipitation of mundulone and MA from a DMSO stock solution at higher concentrations tested in an aqueous organ bath assay (data not shown).…”
Section: Ex Vivo Tocolytic Ability and Lack Of Off-target Effect On Fetal Ductus Arteriosusmentioning
confidence: 89%
“…Based on the in vitro inhibition of Ca 2+ -mobilization from the myometrial cells and in vitro uterine-selectivity compared to aortic VSMCs by mundulone and MA, we chose to examine their tocolytic ability and confirm uterine-selectivity at the tissue level. A well-established and widely utilized ex vivo isometric contractility assay was used to examine the effect of mundulone and MA on contractile activity of term pregnant mouse myometrial tissue [3,[33][34][35][36][37][38][39]. During our initial experiments, we observed the precipitation of mundulone and MA from a DMSO stock solution at higher concentrations tested in an aqueous organ bath assay (data not shown).…”
Section: Ex Vivo Tocolytic Ability and Lack Of Off-target Effect On Fetal Ductus Arteriosusmentioning
confidence: 89%
“…The remaining tissue is stored at 4 °C and used within one 51 or two 52 days of collection. Samples are then further sliced into tissue strips on the order of millimeters, 37,53 often using an oscillating vibroslicer. 49 The length of the strip ultimately depends on the type of analysis that will be performed, whether functional or molecular.…”
Section: In Vivo and Ex Vivo Models Of The Myometriummentioning
confidence: 99%
“…A study by Nani [4] resulted that drinking the soaking water containing a dose of 40 grams of A. hierochuntica L. increased the frequency of uterine contractions [4]. However, until now, the mechanism that regulates myometrial contraction activity during pregnancy, labor, and birth has not been fully observed [16]. Several studies have obtained an overview of the estrogenic effect of phytoestrogens [17].…”
Section: Introductionmentioning
confidence: 99%